Preparation of Al2O3–Y3Al5O12–ZrO2 eutectic ceramic by flash sintering. (15th March 2016) - Liu, Dianguang; Gao, Yan; Liu, Jinling; Liu, Fangzhou; Li, Kai; Su, Haijun; Wang, Yiguang; An, Linan
Abstract: Al2 O3 –Y3 Al5 O12 –ZrO2 ternary eutectic oxide ceramic was prepared by flash sintering the corresponding powder. The highly dense sample was obtained at relatively low temperature and very short time with the assist of dc electric field. As-prepared ceramics well preserve the phase composition and microstructure of the original eutectic powder. The ceramic exhibits relatively high hardness and high fracture toughness. These results clearly demonstrate the feasibility of employing the flash-sintering technique to fabricate eutectic ceramics. Graphical abstract: We have demonstrated that the eutectic powder can be flash sintered, evidenced by the presence of an abrupt increase in power dissipation. The closer observation of the sample sintered at 495 V/cm, 0.3 A reveals that the YAG phase (gray color grains) and Al2 O3 phase (dark color grains) are interweaved together; while the ZrO2 grains (white color) are mainly distributed at the interface between Al2 O3 and YAG phases. The measured toughness for the ceramic is 6.20 ± 0.34 MPa·m 1/2 . Many grain-bridging sites can be clearly observed along the crack wake, indicating the grain bridging is likely responsible for the observed high toughness.